2003
DOI: 10.1373/49.5.808
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Chemiluminometric Assay for Hyperglycosylated Human Chorionic Gonadotropin (Invasive Trophoblast Antigen)

Abstract: Hyperglycosylated human chorionic gonadotropin (HhCG) is a glycoprotein hormone secreted during embryonic implantation and trophoblast invasion of the uterine wall and is an early marker of pregnancy (1 ). Relative to hCG, HhCG has a higher molecular mass (38.5-40 kDa, depending on the amount of carbohydrate) and a higher number of asparagine (N)-linked triantennary carbohydrates and serine (O)-linked tetrasaccharide core structures in the ␤-subunit (2 ). Although both are secreted from the placenta and chorio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Using standard methods of data analysis that have been shown to be robust in the past, we found that ITA performance was essentially equivalent to hCG. For example, among 533 serum ITA measurements collected as part of another study (14 ), there was no such deviation from expected at high ITA concentrations among the unaffected pregnancies, as found in the current study (Fig. 2).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Using standard methods of data analysis that have been shown to be robust in the past, we found that ITA performance was essentially equivalent to hCG. For example, among 533 serum ITA measurements collected as part of another study (14 ), there was no such deviation from expected at high ITA concentrations among the unaffected pregnancies, as found in the current study (Fig. 2).…”
Section: Discussionsupporting
confidence: 59%
“…The monoclonal antibody (B152) specific for ITA used in this assay has minimal cross-reactivity with hCG and is applicable to many sample types, including serum (14 ). Singleton samples were assayed.…”
Section: Methodsmentioning
confidence: 99%
“…This antibody was raised against a choriocarcinoma-derived hCG, and its increased binding may indicate trophoblastic disease (Birken et al 2001), but it may also be useful in detecting risk of pregnancy complications such as early pregnancy loss (Kovalevskaya et al 2002b) and Down syndrome , Pandian et al 2003. A lectin immunoassay using WGA binding on hCG in serum (Abushoufa et al 2000) was not an effective additional marker in screening for Down syndrome in the first trimester (Spencer et al 2002), but it was not tested with urine specimens.…”
Section: Discussionmentioning
confidence: 99%
“…A high proportion of hCG as hCG-h is useful in diagnosing malignant trophoblastic disease (4 ). These results need to be confirmed, but an earlier-version assay for hCG-h is not presently available (5 ). We developed a time-resolved immunofluorometric assay that uses B152 and found that serum contains factors that interfere with the assay to cause falsely low results.…”
Section: To the Editormentioning
confidence: 99%